Sudents’ science manipulative skills during transition from primary to secondary school / Hidayah Binti Mohd Fadzil - Mohd Fadzil, Hidayah (2014)

(untitled)
Manipulative skills and abilities include skills in the handling and manipulation of materials and apparatus in the context of scientific investigation, as well as the ability to follow instructions and make accurate observation. Students lack exposure to hands-on activities at primary level and this could lead to deficiency in manipulative skills and they will carry this problem to secondary school. Transition to secondary school is a challenging process for students whereby they have to adapt with academic, social and emotional issues to fit into their new environment. Thus the purpose of this study was to explore and investigate the acquisition of students‟ manipulative skills during the transition from primary school (end of Year Six) to secondary school (early Form One). A qualitative study was employed in this research. The participants were selected using the purposive sampling technique. This study was conducted for a period of 11 months and involved 10 participants where the same students were tracked during their transition from the end of Year Six in primary school to the middle of Form One in secondary school. The Manipulative Skills in Transition Tasks (MSTT) instrument has been constructed by the researcher and was completed by the students in order to understand their ability in using four (4) scientific apparatus which are the measuring cylinder, thermometer, Bunsen burner and microscope. The primary data collection techniques used in this study were observation of students doing the MSTT tasks, interviews and examination of the students‟ scientific drawing. Data from early, mid and late transition were analyzed using the constant comparative method of data analysis. Two dimensions emerged during data analyses which were technical skills and functional aspects of performing laboratory task. Each dimension can be explained v through the understanding of elements and sub-elements, respectively. The findings described students‟ manipulative skills during transition. Findings indicated that there is a gap in manipulative skills during transition and this needs to be addressed. If not, the gap may impede the students‟ continuity in the acqusition of manipulative skills during early, mid and late transition. The findings also show that students‟ cognitive ability did not reflect their true ability in manipulative skills. Based on the findings, the Meniti Peralihan (MeP) resource guide has been developed. The resource guide provides an appropriate method to identify the students level of competency in manipulative skills during transition. The evaluation of the appropriateness of this resource guide has been conducted on 39 primary and secondary school science teachers. They found the resource guide useful in assisting them to enhance the students‟ maniplative skills during transition. Further collaboration between primary and secondary school should also be considered in order to bridge the gap during transition.